Wage dispersion and wage dynamics within and across firms - Carlos Carrillo-Tudela; Eric Smith (Federal Reserve Bank of Atlanta, 2009)
This paper examines wage dispersion and wage dynamics in a stock-flow matching economy with on-the-job search. Under stock-flow matching, job seekers immediately become fully informed about the stock of viable vacancies. If only one option is available, monopsony wages result. With more than one firm bidding, Bertrand wages arise. The initial and expected threat of competition determines the evolution of wages and thereby introduces a novel way of understanding wage differences among similar workers. The resulting wage distribution has an interior mode and prominent, well-behaved tails. The model also generates job-to-job transitions with both wage cuts and jumps.
Keywords: J31; J63; J64; 330; wage dispersion; wage dynamics; job search; stock-flow matching